System-Level Energy-Aware Design of Cyber-Physical Systems - Isasa, José Antonio Esparza (Technical Report Electronics and Computer Engineering, 2013)
In this technical report we present the work conducted during the first part of the PhD thesis “System-Level Energy-Aware Design of Cyber-Physical Systems”. We present the application of modelling techniques and methodologies to study energy consumption during the design and implementation of cyber-physical systems. This study is made from the electro-mechanical and computation angle. Additionally we present a setup that allows the combination of abstract models with hardware and software preliminary realizations. This allows a stepwise model to implementation transformation and improved model accuracy. Some of these techniques have been applied to the case study e-Stocking and others have been studied with more simple experimental setups. In addition to the scientific content, we also present a description of the envisioned future work and the plans that will lead to completion of this PhD thesis by April 2015.